(untitled) (DAPesquisa, 2025)
The present article intends to present the actions developed by the extension project Maturity (Stage)Scene, whose purpose is the theatrical practice with seniors through workshops, assembly and circulation of shows. Such practice has been based on studies and research in the field of Community Theatre, and seeks to develop in this article some dialogues and approaches between the actions developed by the project and aspects that characterise theatrical practices in communities, with the aim of broadening the discussion in this field of research and deepening the studies and practices that have been carried out within the Extension Project. To this end, the writings of Nogueira (2008), Boal (2011) and Freire (1979; 1987) are used to establish these dialogues and approaches and to demonstrate how the extension project is moving towards a dialogical, collective and collaborative practice, with a focus on the community in which it operates.